Quality Control of Herbal Medicines with Spectrophotometry and Chemometric Techniques - Application to Baccharis L. Species Belonging to Sect - Caulopterae DC. (Asteraceae) - Rodriguez, María Victoria; Martínez, María Laura; Cortadi, Adriana; Campagna, María Noel; Sapio, Osvaldo Di; Derita, Marcos; Zacchino, Susana; Gattuso, Martha (IntechOpen, 2012)
None